1994
DOI: 10.1063/1.468500
|View full text |Cite
|
Sign up to set email alerts
|

Study of the ArBr−, ArI−, and KrI− anions and the corresponding neutral van der Waals complexes by anion zero electron kinetic energy spectroscopy

Abstract: Three rare gas halide (RgX−) anions, ArBr−, ArI−, and KrI−, and the corresponding open-shell van der Waals complexes, ArBr, ArI, and KrI, were studied with anion zero electron kinetic energy (ZEKE) spectroscopy. Photodetachment of each anion accesses the three lowest-lying electronic states (the X1/2, I3/2, and II1/2 states) of the neutral complex. The spectra for each system reveal well-resolved progressions in the low frequency vibrations of the anion and the three neutral electronic states, providing a deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
1
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 72 publications
8
119
1
3
Order By: Relevance
“…The calculated equilibrium bond length at CCSD(T)/BS3 level is little lower than the experimental value of Zhao et al, but the dissociation energy and rotational constant agree well with the experimental values. It may be noted that the equilibrium bond length obtained at CCSD(T)/BS2 level is very close to the experimental value [1]. The equilibrium bond length calculated by Buchachenko et al [8] is higher than that of ours.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The calculated equilibrium bond length at CCSD(T)/BS3 level is little lower than the experimental value of Zhao et al, but the dissociation energy and rotational constant agree well with the experimental values. It may be noted that the equilibrium bond length obtained at CCSD(T)/BS2 level is very close to the experimental value [1]. The equilibrium bond length calculated by Buchachenko et al [8] is higher than that of ours.…”
Section: Resultssupporting
confidence: 73%
“…ground state are displayed in Table 3 along with other theoretical and experimental values. It can be noted that the experimental equilibrium bond length quoted by Batsanov et al is higher than that reported by Zhao et al [1]. The calculated equilibrium bond length at CCSD(T)/BS3 level is little lower than the experimental value of Zhao et al, but the dissociation energy and rotational constant agree well with the experimental values.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Because the P 3/2 component of iodine is degenerate (in contrast to P 1/2 ), it is reasonable to explain this structure by the lifting of this degeneracy. This effect has been found for most of the iodine-containing van der Waals clusters studied so far [e.g., ArI, KrI (Zhao et al, 1994), I(CO 2 ) (Zhao et al, 1993)] by high-resolution anion ZEKE. The observed energy splitting is between 30 -300 cm…”
mentioning
confidence: 78%
“…Neither scaling the depth of ab initio interaction potentials and shifting of their equilibrium distances, nor replacing the neutral potentials by the empirical scattering potentials from ref 18 improves the situation noticeably. Likewise, rotationally resolved simulations that used rotational line strength factors 3,20 failed to produce better agreement with the measurements in the region above 13000 cm -1 . These efforts suggest that the discrepancies between the measured and simulated spectra mostly originate from the photodetachment transition probability calculations.…”
Section: S(e)mentioning
confidence: 97%